Digital (in)equalities and user emancipation: Examining the potential of Adorno's maxim of Mündigkeit for critical intergenerational learning - Leontowitsch, Miranda; Wolf, Friedrich; Oswald, Frank (Frontiers in Sociology, 2022)
The widespread use of mobile technologies has penetrated the lives of people across all age groups with the usage of smartphones and wareables appearing ‘natural’ and without alternatives. The digitalisation of everyday life means that communication and negotiation of social and societal meanings are co-constructed by users and mobile technologies thereby blurring the boundary between on- and off-line as well as social and private spheres. At the same time, the global-market logic that has driven the extent and speed of this social transformation raises questions as to how individuals retain influence and agency over the digital technologies that have come to define both social and private spheres and that surround them at all times. Against this backdrop, this theoretical paper discusses the role of Adorno’s maxim of emancipation towards autonomy (Mündigkeit) for education (Erziehung) and critical learning about and living with digital technologies. The paper suggests a way forward through intergenerational learning as a didactical method of enhancing emancipation among younger and older generations of ‘users’ in their joint efforts of becoming critical agents in an age of digitally enhanced data markets.